On the Single-Molecule Magnetic Behavior of Linear Iron(I) Arylsilylamides - Weller, Ruth; Atanasov, Mihail; Demeshko, Serhiy; Chen, Ting-Yi; Mohelsky, Ivan; Bill, Eckhard; Orlita, Milan; Meyer, Franc; Neese, Frank; Werncke, C Gunnar (Inorganic chemistry, 2023)
The rational design of 3d-metal-based single-molecule magnets (SMM) requires a fundamental understanding of their intrinsic electronic and structural properties and how they translate into experimentally observable features. Here, we determined the magnetic properties of the linear iron(I) silylamides Kcrypt[FeL ] and [KFeL ] (L = -N(Dipp)SiMe ; crypt = 4,7,13,16,21,24-Hexaoxa-1,10-diazabicyclo[8.8.8]hexacosan). For the former, slow-relaxation of the magnetization with a spin reversal barrier of = 152 cm as well as a closed-waist magnetic hysteresis and magnetic blocking below 2.5 K are observed. For the more linear [KFeL ], in which the potassium cation is encapsulated by the aryl substituents of the amide ligands, the relaxation barrier and the blocking temperature increase to = 184 cm and = 4.5 K, respectively. The increase is rationalized by a more pronounced axial anisotropy in [KFeL ] determined by dc-SQUID magnetometry. The effective relaxation barrier of [KFeL ] is in agreement with the energy spacing between the ground and first-excited magnetic states, as obtained by field-dependent IR-spectroscopy (178 cm ), magnetic measurements (208 cm ), as well as theoretical analysis (212 cm ). In comparison with the literature, the results show that magnetic coercivity in linear iron(I) silylamides is driven by the degree of linearity in conjunction with steric encumbrance, whereas the ligand symmetry is a marginal factor.